Reorientation of Islamic Religious Education in the Global Era in Facing the Challenges of Globalization, Multiculturalism, and Radicalism - Mukhlis Mukhlis; Syaifuddin Sabda; Husnul Yaqin; Hamdan Hamdan (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to discuss the reorientation of Islamic Religious Education in the global era in addressing the challenges of globalization, multiculturalism, and radicalism. Globalization brings the flow of values, cultures, and information that can affect the religious identity and moral values of the younger generation, while multiculturalism demands the ability to coexist in a pluralistic society, and radicalism emerges as a consequence of narrow and exclusive religious understanding. The reorientation of PAI is necessary so that religious education is not merely ritualistic but also reflective, humanistic, and contextual. This study employs a library research approach, based on the review of articles, journals, and other scholarly works related to the keywords, with searches conducted on Google Scholar and assisted by the Publish or Perish (POP) application to find similar studies. The findings indicate that the reorientation involves the strengthening of universal Islamic values, the development of tolerant and inclusive attitudes, and the prevention of radicalism through religious moderation and character education